How prior experience with pitch accents shapes the perception of word and sentence stress. Issue 1 (2nd January 2022) - Kutscheid, Sophie; Zahner-Ritter, Katharina; Leemann, Adrian; Braun, Bettina
ABSTRACT: Listeners perceive high or rising pitch as stressed – at the word and sentence level (high-pitch bias). Since stressed syllables can also be low-pitched, this bias may lead to misinterpretations of word and sentence stress and thus slow down speech comprehension. We investigate the effect of immediate exposure with high- vs. low-pitched stressed syllables on the identification of word and sentence stress. Participants were exposed to utterances containing only high- vs. low-pitched stressed syllables. In experimental trials, they then heard either trisyllabic words with word stress on the second syllable (Experiment 1) or three-word-sentences with sentence stress on the second word (Experiment 2) and indicated the position of word/sentence stress. Stimuli were presented in three intonation conditions (high-pitched first, second, or third syllable/word). Both experiments endorsed the high-pitch bias, with an increase after high-pitch exposure. Our results suggest a speaker-independent re-weighting of acoustic cues to stress, which is driven by experience.